Suicidal ideation across race in a justice‐involved sample: An item response theory approach. Issue 3 (2nd December 2020) - Ruchensky, Jared R.; Balsis, Steve; Edens, John F.; Douglas, Kevin S.
Abstract: Objectives: Compared to community samples, rates of suicide are much higher in forensic and correctional settings, yet limited research has focused on the development and improvement of suicide assessment methods used in such contexts. Moreover, despite evidence that suicide assessment varies across Caucasians and African Americans, to our knowledge this important issue has received little attention within higher risk correctional samples. We used Item Response Theory and Differential Item Functioning analyses to address this gap within the literature. Method: Specifically, we examined the psychometric properties of the Suicidal Ideation scale of the Personality Assessment Inventory (Morey, 2007) in a large sample of justice‐involved individuals. Results: Caucasians report greater suicidal ideation compared to African American participants on average. However, after controlling for mean differences, Caucasians and African Americans differentially endorsed symptoms of suicidal ideation. If the level of suicidal ideation is held constant across racial categories, Caucasians underreported suicidal ideation relative to African Americans. Conclusion: Results suggest a nuanced picture of suicidal ideation across racial categories that can be informed by Item Response Theory approaches to scale construction and refinement.